Bricked subwavelength structures: a flexible metamaterial topology - Luque-González, José Manuel; Ortega-Moñux, Alejandro; Halir, Robert; Molina-Fernández, Íñigo; Wanguemert-Pérez, Juan Gonzalo; Cheben, Pavel; Schmid, Jens H. (My University, 2021)
Subwavelength gratings (SWG) are periodic structures that synthesize lithography tailorable metamaterials with desired permittivity, dispersion, and anisotropy, enabling the design of a myriad of high-performance devices. Here we present our latest SWG geometrical topology which not only provide more control over the synthesized material but also alleviate the required fabrication resolution to fabricate SWG structures.
Keywords: Telecomunicaciones; Estructuras; Ingeniería de telecomunicaciones; Silicon-on-insulator; Subwavelength grating structures; Dielectric metamaterial; Multimode interferometer